Self-employment and poverty in developing countries: Helping the self-employed earn more for the work they do - Gary S. Fields (IZA World of Labor, 2014)
A key way for the world's poor—nearly half of humanity—to escape poverty is to earn more for their labor. Most of the world's poor people are self-employed, but because there are few opportunities in most developing countries for them to earn enough to escape poverty, they are working hard but working poor. Two key policy planks in the fight against global poverty should be: raising the returns to self-employment and creating more opportunities for poor people to move from self-employment into higher paying wage employment.
Keywords: J23; 330; self-employment; poverty; labor earnings